The obesity supine death syndrome (OSDS). (13th December 2017) - Lemyze, M.; Guiot, A.; Mallat, J.; Thevenin, D.
Summary: The obesity supine death syndrome refers to a catastrophic cascade of cardiorespiratory complications resulting from the supine positioning of a morbidly obese subject which can ultimately lead to death. It was first described in 1977 in two massively obese patients who were forced to lie down for medical procedures. But surprisingly, despite the current worldwide epidemic of obesity, very few cases have been reported yet. It can be assumed that the syndrome is poorly recognized in clinical practice and may participate in the high rate of unexplained death in morbidly obese patients. Based on the previously published cases and on those we met, this review aims at helping clinicians to early detect at‐risk patients, to correctly diagnose this dramatic syndrome and to understand the underlying pathophysiology. More importantly, the main objective is to convince the attending clinicians that they have to do everything in their power to prevent obesity supine death syndrome occurrence by maintaining morbidly obese patients in the sitting or upright position whenever possible. When the syndrome unfortunately occurs, the best therapeutic approach is based on the immediate return to sitting position.